Early Childhood Education Teacher Training Effectiveness Study - HAN, SHU (Pacific International Journal, 2024)
Since 2019, China has endorsed a series of initiatives supporting the training of early childhood education teachers. With numerous higher vocational institutions introducing early childhood education programs, there is a growing interest in assessing the effectiveness of short-term training. This study investigates the efficacy of early childhood education training methods by conducting a satisfaction survey among students. It examines the interconnections between effectiveness and political, economic, and cultural factors. Employing a questionnaire survey approach, participants include undergraduate students majoring in early childhood education, interns, teachers in early childhood education institutions, and university faculty members.